Comparative foraging ecology of macaroni and rockhopper penguins at the Prince Edward Islands - Whitehead, Thomas Otto (Percy FitzPatrick Institute of African Ornithology, 2018)
Penguins are one of the largest consumers of marine resources in the Southern Ocean and spend most of their lives at sea. Although the last four decades have seen technological advancements that have considerably expanded our knowledge about their at-sea behaviour, there is still much to be learned. Given the rapid ongoing ecosystem changes in the Southern Ocean, it is vital to better understand, firstly, how penguins respond to environmental variability, and secondly, how such changes alter ecological relationships between sympatric species. Being flightless, travel is slower and more costly for penguins than flying seabirds. This constrains their ability to find resources, particularly during the breeding season when they must regularly return to the colony to provision offspring. As penguins are colonial nesters, high foraging pressure near the colony can limit available resources, enhancing potential intra- and interspecific competition. At many localities, ecologically similar penguin species breed sympatrically. In such cases, co-existence is only thought possible through ecological segregation in space, time and/or diet. At the Prince Edward Islands, approximately 302,000 pairs of macaroni Eudyptes chrysolophus and 80,000 pairs eastern rockhopper E. chrysocome filholi penguins breed sympatrically. These populations are closer to parity than at any other locations where two eudyptid species breed sympatrically. Populations of both species at the Prince Edward Islands have declined in the last two decades, but drivers of these declines are poorly understood. The primary aim of this thesis was to better understand the foraging strategies of macaroni and rockhopper penguins at the islands and identify aspects of their ecology that allow them to co-exist. The secondary focus was to investigate how each species responds to environmental variability and assess how ecological interactions between species might be altered in an era of rapid global change. To study the at-sea habitat use and diving behaviour of penguins during chick-rearing and pre-moult periods, I used GPS loggers and time-depth recorders. To track penguins during the winter I used geolocation loggers and satellite transmitters. Stable isotope analyses were used to investigate trophic ecology during late winter, summer and pre-moult periods. During the breeding season, both species primarily foraged in pelagic waters beyond the shelf break (> 3000 m), with macaroni penguins foraging slightly farther offshore on average. However, rockhopper penguins breeding adjacent to the inter-island shelf foraged in shallow waters (< 200 m) over the shelf. Both species dived to similar depths (40 to 60 m), but macaroni penguins dived deeper more often. The diet of both species was dominated by two krill species (Thysanoessa vicina and Euphausia vallentini). Diving behaviour varied between years, with both species diving deeper when the SAF was located farther away and geostrophic flow was reduced. During these conditions, macaroni penguins fed on a larger proportion of myctophids whereas rockhopper penguins resorted to less energy-dense nototheniids. This highlights contrasting responses to periods of low krill availability. During the pre-moult period, habitat preferences were similar between species, with penguins travelling up to 1000 km south to forage in Antarctic Zone waters (SST 3-4 °C). However, a three-week difference in departure dates minimised spatiotemporal overlap between species. Diving behaviour was similar between species, but macaroni penguins performed more deep dives and encountered thermoclines more often. Stable isotope analyses revealed that macaroni penguins fed on a greater proportion of fish than rockhopper penguins, and revealed species-specific spatial responses to changes in primary productivity, with macaroni penguins travelling farther south in less productive years. During the 6-month long winter sojourn, macaroni penguins generally foraged in cooler waters (SST ~ 3 °C) compared to rockhopper penguins (5-6 °C). However, stable isotope analyses revealed that trophic and spatial overlap were high during late winter. Both species associated with mesoscale eddies and submesoscale filaments, suggesting that these features play an important role in aggregating prey during the resource-limited winter months. In summary, it appears that subtle differences exist to minimise competitive overlap between macaroni and rockhopper penguins. The three-week difference in the onset of breeding is integral to minimising competitive overlap during late winter, brood-guard/crèche, pre-moult and immediately following the moult. This allochrony staggers the peak energy demands of rockhopper penguins to reduce overlap with macaroni penguins. The larger-bodied macaroni penguins are capable of diving deeper, for longer and more efficiently than rockhopper penguins, which increases their behavioural flexibility and fitness by minimising stresses associated with reduced krill availability. Such differences in diving behaviour may explain contrasting population trends at the islands and suggests that rockhopper penguins may continue to decline at a faster rate than macaroni penguins if ongoing climate change continues to reduce prey availability around the Prince Edward Islands.